Severe root resorption resulting from orthodontic treatment: Prevalence and risk factors - Maués,Caroline Pelagio Raick (2015)
OBJECTIVE: To assess the prevalence of severe external root resorption and its potential risk factors resulting from orthodontic treatment. METHODS: A randomly selected sample was used. It comprised conventional periapical radiographs taken in the same radiology center for maxillary and mandibular incisors before and after active orthodontic treatment of 129 patients, males and females, treated by means of the Standard Edgewise technique. Two examiners measured and defined root resorption according to the index proposed by Levander et al. The degree of external apical root resorption was registered defining resorption in four degrees of severity. To assess intra and inter-rater reproducibility, kappa coefficient was used. Chi-square test was used to assess the relationship between the amount of root resorption and patient's sex, dental arch (maxillary or mandibular), treatment with or without extractions, treatment duration, root apex stage (open or closed), root shape, as well as overjet and overbite at treatment onset. RESULTS: Maxillary central incisors had the highest percentage of severe root resorption, followed by maxillary lateral incisors and mandibular lateral incisors. Out of 959 teeth, 28 (2.9%) presented severe root resorption. The following risk factors were observed: anterior maxillary teeth, overjet greater than or equal to 5 mm at treatment onset, treatment with extractions, prolonged therapy, and degree of apex formation at treatment onset. CONCLUSION: This study showed that care must be taken in orthodontic treatment involving extractions, great retraction of maxillary incisors, prolonged therapy, and/or completely formed apex at orthodontic treatment onset.